EVALUATION OF THE JUMAT TAQWA PROGRAM (JUMTAQ) TO CONSTRUCTING THE RELIGIOUS CHARACTER OF STUDENTS - Ida Ida (Nurul Jadid University, 2021)
This study describes the Evaluation of the Jumat Taqwa Program at SMAN 13 Pandeglang. The purpose of this study is to evaluate the Jumat Taqwa program, which is routinely held every Friday morning at SMAN 13 Pandeglang as a consideration for the student and spiritual fields, to take policies regarding the development of character education in schools. This study uses a qualitative descriptive method with the evaluation model used is Countenance Stake. The result of this study is that the Jumat Taqwa program (JUMTAQ) at SMAN 13 Pandeglang received a good response from the students. This can be seen based on the percentage of students who agree and are enthusiastic about participating in the Jumtaq program, 89%. The average answer of students in the aspect of aqidah after participating in the Jumat taqwa program 92% said consistently, and 8% often said, in the element of morality there were 78% always, 14% usually and 8% sometimes, while in the aspect of increasing knowledge of fiqh the answers were obtained Yes by 87% and No by 13%. Based on the study results, the Jumat Taqwa program made a positive contribution to the cultivation of the religious character of students.